Engineering Behaviour of Clay Shale Stabilized with Asphalt Emulsion and Artificial Lightweight Aggregate Perlite - Naess, Victor Firstkiel Feber (Jurnal Sosial Teknologi, 2025)
Soil plays a vital role in the planning stage of road construction. The subgrade, representing the final construction that receives the vehicle load transmitted by the pavement, is of critical importance. Clay shale is among the most challenging soil types due to its susceptibility to weathering when exposed to water or air. In the wake of geotechnical challenges precipitated by clay shale soil, there arises a pressing need for soil stabilization initiatives aimed at enhancing the soil's physical properties. The present study utilizes two stabilization materials: asphalt emulsion and artificial light weight aggregate perlite. The initial soil physical properties and mechanical properties (Unconfined Compressive Strength Test) were obtained through laboratory testing. Preliminary findings from rigorous testing and in-depth analysis have yielded notable results. The highest ultimate unconfined compressive strength value, as determined by a 14-day curing period with an asphalt content of 8% and an artificial light weight aggregate of 1%, has been recorded at 2,301 kg/cm2.